Новые антропологические материалы из могильника у с. Лучистое - Радочин, В.Ю. (Материалы по археологии, истории и этнографии Таврии, 2002)
Настоящая работа посвящена вводу в научный оборот новых антропологических данных, полученных в результате археологических раскопок северо-западного участка могильника у с. Лучистое в 2000 году. В работе учтены также некоторые материалы исследований того же некрополя, проводившиеся в 1984 и 1995 г This article is devoted to the introduction of new anthropological materials obtained as a result of archaeological excavations near the village of Luchistoe in 2000. This expedition was headed by A.I.Aibabin. The material from 26 burial constructions (15 individual burials and 11 vaults) was processed. Within the craneological group under consideration sexual demorphism is rather clearly traced. Four cases of artificial deformation of craniums; no cases are observed in the burials of this cemetery dating back to the earlier periods. It should be noted that there were diseases of dental system and locomotor system. According to the obtained data average age for men was 38 - 40 years, which is less if we compare that with the average age for women (40-42) and is rather an unusual fact for this period. 41% of buried children were 6-8 years old. The newly obtained material and the analysis of previous research enable us to consider those burials to be family burial vaults